2005
DOI: 10.1111/j.1365-2486.2005.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use and land cover change on groundwater recharge and quality in the southwestern US

Abstract: Humans have exerted large-scale changes on the terrestrial biosphere, primarily through agriculture; however, the impacts of such changes on the hydrologic cycle are poorly understood. The purpose of this study was to test the hypothesis that the conversion of natural rangeland ecosystems to agricultural ecosystems impacts the subsurface portion of the hydrologic cycle by changing groundwater recharge and flushing salts to underlying aquifers. The hypothesis was examined through point and areal studies investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
363
0
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 584 publications
(401 citation statements)
references
References 52 publications
21
363
0
17
Order By: Relevance
“…Not surprisingly then, ecohydrological research originally focused on areas that experience either seasonal water limitation (Rodriguez-Iturbe, 2000;Porporato et al, 2003;Huxman et al, 2004Huxman et al, , 2005Scott et al, 2006) or rapidly changing vegetation (e.g. due to agriculture, logging or disturbance) Scanlon et al, 2005). The semiarid southwestern United States is an example of a water-limited region where climate change is altering the amount, timing and form of precipitation (Mote et al, 2005) and model projections suggest a much drier future (Seager et al, 2007).…”
Section: Develop Distributed Field Data Setsmentioning
confidence: 99%
“…Not surprisingly then, ecohydrological research originally focused on areas that experience either seasonal water limitation (Rodriguez-Iturbe, 2000;Porporato et al, 2003;Huxman et al, 2004Huxman et al, , 2005Scott et al, 2006) or rapidly changing vegetation (e.g. due to agriculture, logging or disturbance) Scanlon et al, 2005). The semiarid southwestern United States is an example of a water-limited region where climate change is altering the amount, timing and form of precipitation (Mote et al, 2005) and model projections suggest a much drier future (Seager et al, 2007).…”
Section: Develop Distributed Field Data Setsmentioning
confidence: 99%
“…[11] Agricultural development has resulted in increased deep drainage rates (water flux below the root zone as opposed to recharge at the water table) across the High Plains and has recharged the aquifer in parts of the central and southern High Plains, as shown by rising groundwater levels by up to 23 m [Luckey and Becker, 1999;Scanlon et al, 2005]. Increases in recharge on some other areas may be masked by depletion related to groundwater-based irrigation.…”
Section: Background To Study Areamentioning
confidence: 99%
“…Gee & Hillel (1988) and Allison et al (1994) have listed several approaches for estimating groundwater recharge from natural rainfall and irrigation, and summarized the relative merits. The chloride ion, which is characterized by its conservation, low cost and being pollution-free, has been widely applied in groundwater recharge studies in arid and semi-arid regions (Bazuhair & Wood, 1996;Bromley et al, 1997;Scanlon et al, 2005). Previous studies have shown that many arid regions have experienced little or no direct recharge for millennia (Allison et al, 1990;Scanlon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%